Helicobacter pylori cytotoxin-associated gene A virulence and its association with the epithelial-mesenchymal transition in gastric cancer - Dudek, Iga; Forma, Alicja; Hamerska, Justyna; Flieger, Michał; Januszewski, Jacek; Cywka, Tomasz; Kozak, Joanna; Baj, Jacek (Journal of Education, Health and Sport, 2022)
Gastric cancer is currently one of the most prevalent malignancies worldwide with a high mortality rate. Helicobacter pylori (H. pylori) infection significantly contributes to the onset and progression of gastric cancer mainly due to the induction of chronic inflammatory responses. The pathogenicity of H. pylori is associated with a vast number of virulence factors among which cytotoxin-associated gene A (CagA) plays a crucial role. We conducted a literature review of PubMed, Web of Science, and Scopus on September 1st, 2021. There were no limits regarding the year and the language of publication. Articles included in this review concerned human and animal studies. The following search string was applied during the search: (gastric cancer) AND (epithelial-mesenchymal transition) AND (Helicobacter pylori) AND (cytotoxin-associated gene A). The final analysis included 135 articles independently reviewed by the authors. H. pylori CagA-positive strains seem to be more virulent compared to the CagA-negative strains. CagA pathogenicity includes the increased secretion of pro-inflammatory cytokines, induction of cancer stem cell-like properties, apoptosis prevention, or overactivation of particular oncogenic pathways. H. pylori might induce epithelial-mesenchymal transition (EMT) via numerous pathways, among which CagA-related pathogenicity is considered to be of high significance. Mechanisms associated with CagA action are involved in the maintenance of chronic H. pylori infection, subsequent EMT induction, and further onset and progression of gastric cancer. Because of a huge number of H. pylori strains with different virulence mechanisms, the clinical outcome of patients is also associated with the particular type of strain that infected a patient.